化简:9x+6x的平方-3(x-2/3x)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 07:50:13
化简:9x+6x的平方-3(x-2/3x)化简:9x+6x的平方-3(x-2/3x)化简:9x+6x的平方-3(x-2/3x)9x+6x的平方-3(x-2/3x)=6x^2+9x-3(1/3x)=6x
化简:9x+6x的平方-3(x-2/3x)
化简:9x+6x的平方-3(x-2/3x)
化简:9x+6x的平方-3(x-2/3x)
9x+6x的平方-3(x-2/3x)
=6x^2+9x-3(1/3x)
=6x^2+9x-x
=6x^2+8x
化简(x+2)(x的平方-6x-9)-(x-5)(x-3)x
(4x+20)(x的平方-6x+9)/(3x-x的平方)(x的平方+2x-15)
化简:9x+6x的平方-3(x-2/3x)
x的平方-6x+9/9-x的平方÷2x-6/x的平方+3x
x的平方-6x+9/9-x的平方÷2x-6/x的平方+3x
(X的平方+9x)/(x的平方+3x)+(x的平方-9)/(x的平方+6x+9)
解方程(x-2)X(x的平方-6x-9)=x(x-5)X(x-3)
X(x平方-6x-9)-x(x平方-8x-15)+2x(3-x)其中x=-六分之一
(1-x/3-x)平方除以x平方-6x+9/9-x平方*1/x平方-2x+1
(x-1/x平方-6x+9)-(1/x-3)-(2x/9-x平方)
2X的平方-6x/X的平方-9-x+3/3-X-2X+6/x的平方+6x+9=3
x+3/x+1·2x的平方+6x/x的平方+6x+9-x/x+1,其中x=2
x-3分之-2+x+x的平方除以x的平方-6x+9分之x+2
[(x的 2次方+6x+9)除(x+3)](x的平方-3x+9)
数学计算(9x平方-6x+1)÷(x-2)×(2x-(x)的平方)÷(3x-1)
先化简再求值:(x+2)(x的平方-6x-9)-x(x-3)(x-5)其中x=三分之一
化简:2x的平方-4分之3(4x-6x的平方)+(x-3x的平方)
5x的平方+4-3x的平方-5x-2x的平方-5+6x 化简~